Refirming Understanding About Arabic Curriculum Management: Concept, Characteristics, and Study Area - Sembodo Ardi Widodo; Agung Setiyawan (LISANIA: Journal of Arabic Education and Literature, 2021)
This article aims to reinforce the understanding of the concepts, characteristics, and scope of studies in Arabic language curriculum management. This type of research includes library research, which is a descriptive qualitative research. The data was collected using the documentation method. Meanwhile, data analysis was carried out through qualitative (non-statistical) analysis methods on the basis of which conclusions were drawn using an inductive frame of mind. The results show that the Arabic language curriculum management is a distinctive process consisting of planning, organizing, directing and controlling actions carried out on the implementation of the Arabic language curriculum by utilizing all existing supporting aspects in order to achieve effective, efficient and optimal goals in accordance with which have been set. The characteristic or characteristic of Arabic language curriculum management is that it contains religious values, either real or cultural values. The scope of operational problems which are the Arabic language curriculum management studies, namely: Management planning and curriculum development; Management of curriculum implementation; Supervision of curriculum implementation; Curriculum monitoring and assessment; Curriculum improvement; Decentralization and curriculum centralization; and labor issues.